Pengaruh Kemudahan Penggunaan E-Commerce dan Diskon Terhadap Keputusan Pembelian Tiket Event Berbasis Online Pada Situs Tokoevent - Pramesti, Kadek Intan; Asmarani, I Gusti Ayu Ratih; Sukariyanto, I Gede Made (Journal of Event and Convention Management, 2024)
This study aims to analyze the influence of e-commerce usability and discount factors on the online purchasing decisions of event tickets on the Tokoevent website. The research methodology encompasses surveys, literature reviews, and interviews. Surveys were conducted among Tokoevent website users to gather data on their perceptions of e-commerce platform usability and the impact of discounts on purchasing decisions. Additionally, literature reviews were employed to formulate theoretical foundations and research hypotheses, while interviews provided in-depth insights from users who had purchased event tickets through the Tokoevent website. Data were analyzed using regression analysis to test the relationship between independent and dependent variables. The findings of this study contribute to an understanding of the factors influencing online event ticket purchasing decisions, thus offering insights for the development of marketing strategies on similar e-commerce platforms.